Europa skończona? - Napieralski, Jędrzej (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The notion of ‘Europe’ is commonly associated with the European Union. This tendency reflects the importance of the EU on the international political arena. However, despite being such a power, the European Union is not always able to tackle all difficulties it faces, including the so-called ‘four deficiencies’: economic, political management, sense of security and ideology. The main question this paper has attempted to answer was the way the word ‘finite’ should be understood: as ‘without future’ or rather ‘perfect’.